2010
DOI: 10.1007/s12032-010-9661-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of serum level of soluble CD44 and IFN-γ in B-cell chronic lymphocytic leukemia

Abstract: Evidence indicates that the slowly expanding population of B cells that characterizes chronic lymphocytic leukemia (CLL) results primarily from defects in responses to cytokines. We evaluated the prognostic value of soluble CD44 and IFN-γ in B-cell chronic lymphocytic leukemia (B-CLL) and analyzed their source and regulation secretion in B-CLL clones in vitro. Levels of soluble CD44 standard (sCD44s) and IFN-γ were analyzed by enzyme-linked immunosorbent assay. B-CLL cells were separated and stimulated in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In agreement with this hypothesis, PD-L1 is inducible in lymphoid cells after treatment with IFN-γ, 43 a cytokine with elevated levels in the serum of CLL patients. 44 Within CLL LN, PD-L1 expression was higher in general and displayed two distinct patterns. The first was characterized by an intense and homogenous expression, while the second was characterized by a more focalized expression inside the PC.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this hypothesis, PD-L1 is inducible in lymphoid cells after treatment with IFN-γ, 43 a cytokine with elevated levels in the serum of CLL patients. 44 Within CLL LN, PD-L1 expression was higher in general and displayed two distinct patterns. The first was characterized by an intense and homogenous expression, while the second was characterized by a more focalized expression inside the PC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that surface PD-L1 expression strongly correlates with lymphocytic infiltration and intratumoral IFNγ production [36] . Additionally, IFNγ is elevated in the serum of CLL patients [37] . Moreover, lenalidomide, an immunomodulatory drug used in CLL therapy, has been shown to induce the production of proinflammatory cytokines, including IFNγ [14,38] .…”
Section: Discussionmentioning
confidence: 99%
“…Published results 16,43 and our in silico meta-analysis (supplemental Figure 1A and Table 2) support both of these findings. Available reports on surface vs soluble and on CD44s vs CD44v isoforms in CLL 37,[43][44][45][46][47][48][49][50] show in their entirety no clear-cut prognostic associations. However, they implicate a higher CD44 turnover in CLL over normal lymphocytes, especially in more aggressive disease subsets.…”
Section: Discussionmentioning
confidence: 99%